Lithium metal negative electrode, preparation method and lithium battery
By introducing MXY material into the lithium metal negative electrode of the lithium metal battery, a solid electrolyte with high ion conduction capability is formed, which solves the problem of lithium dendrites and lithium ion transmission capabilities, and improves the safety and cycle stability of the lithium battery.
Patent Information
- Application Number
- CN202510095125.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-21
AI Technical Summary
After multiple charges and discharges of existing lithium metal batteries, an inert SEI film grows on the surface of the lithium metal negative electrode, hindering the transmission of Li+, resulting in lithium dendrites and battery safety issues, and it is impossible to solve the problem of lithium dendrites and lithium ion transmission capabilities at the same time.
By introducing MXY material as an additive in lithium metal, a mixture containing Li, LiM alloy, LicX, LiY and LiaXYb is formed, and X and Y elements (such as oxygen, nitrogen and halogen) are used to generate solid electrolytes with high ion conduction capabilities, improving the transmission of lithium ions and the safety of the battery.
It realizes rapid transmission and uniform deposition of lithium ions, reduces interface polarization, improves anti-dendrite capability, and improves the safety and cycle stability of lithium batteries.
Smart Images

Figure CN119786613A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials, and in particular relates to a lithium metal negative electrode, a preparation method and a lithium battery. Background Art
[0002] Lithium metal anode has a high theoretical specific capacity (3860 mAh g -1 ), low electrochemical redox potential (3.04 V vs SHE) and low density (0.53 g cm -3 ), is considered to be the "holy grail" of negative electrode materials for next-generation secondary lithium batteries.
[0003] At present, there are still many problems with lithium metal batteries: after repeated charge and discharge of the battery, an inert SEI film grows on the surface of the lithium metal negative electrode, which seriously hinders the + The transmission speed at the interface causes lithium to nucleate at the interface and then grow into lithium dendrites that pierce the electrolyte layer, causing a short circuit and battery safety issues. In addition, lithium metal also has the strongest reducibility. When lithium metal comes into contact with solid electrolytes (sulfides, halides, polymer electrolytes), chemical reactions of varying degrees will occur; and, driven by electrochemistry, a large amount of LiM alloys and M metals with strong electronic conductivity are generated, accompanied by the generation of polysulfide interface phases with low ionic conductivity.
[0004] In order to reduce interfacial polarization and inhibit lithium dendrites, alloying and surface passivation are currently commonly used methods. For example, LiAl and LiIn alloys are prepared. However, alloying cannot effectively solve the dendrite problem. Pretreatment of the lithium metal surface is, to a certain extent, the simplest and most direct strategy. It only requires the use of artificial intervention to pre-generate a layer of artificial SEI on the surface of lithium metal. However, this layer of SEI is usually composed of lithium alloys and lithium salts. The SEI film modified on the surface of lithium metal will increase the interface impedance, resulting in obstruction of lithium ions and reducing the lithium ion transmission capacity at the interface. During the battery charging and discharging process, lithium ions are difficult to quickly pass through the SEI film, and grow on the electrolyte side, causing the battery to short-circuit. Summary of the invention
[0005] In view of the above deficiencies in the prior art, an object of the present invention is to provide a lithium metal negative electrode, a preparation method and a lithium battery to solve the problem that the existing methods cannot simultaneously solve the problem of lithium dendrites and lithium ion transmission capacity.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a lithium metal negative electrode comprising Li, LiM alloy, Li c X, LiY and Li a XY b, where M is a metal element, X is an oxygen element or a nitrogen element, and Y is a halogen; when X is an oxygen element, a=3, b=1, c=2; when X is a nitrogen element, a=5, b=2, c=3.
[0007] Preferably, M is selected from one or more of La-based elements, In, Al, Bi, Zr, Hf, Sn, and Ge.
[0008] In another aspect, the present invention provides a method for preparing a lithium metal negative electrode, comprising the following steps: The lithium metal is heated and melted to obtain molten lithium liquid; Adding an additive to the molten lithium solution, carrying out a heat preservation reaction, and obtaining a lithium metal negative electrode after cooling; the additive is MXY, wherein M is a metal element, X is an oxygen element or a nitrogen element, and Y is a halogen.
[0009] Preferably, the additive is at least one of LaOCl, InOCl, BiOCl, and AlOCl.
[0010] Preferably, the additive is at least one of ZrNCl, SnNCl, HfNCl, and GeNCl.
[0011] Preferably, the amount of the additive added is 2-20% of the mass of the lithium metal, and more preferably 10%.
[0012] Preferably, the temperature of the thermal insulation reaction is 200-350°C.
[0013] Preferably, the reaction time of the insulation reaction is 5-60 min, more preferably 30 min.
[0014] In a third aspect, the present invention provides a lithium battery, which is a lithium metal battery and includes the lithium metal negative electrode as described in the first aspect.
[0015] Preferably, the electrolyte of the lithium battery is Li 7-x PS 6-x Cl x (0.5≤x≤2), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li7P2S8I、Li 10 GeP2S 12 One or more of the following, the positive electrode material of the lithium battery is LiNi m Co n Mn z O2 (m + n + z = 1).
[0016] The beneficial effects of the present invention are: The present invention introduces MXY material as an additive into lithium metal, and utilizes the reaction between MXY material and lithium metal to generate Li, LiM alloy, Li c X, LiY, Li a XY b Due to the introduction of X and Y elements, namely O or N and halogen, a Li3OY or Li5NY2 solid electrolyte is generated, which has a high ion conductivity. Different from the traditional preparation of SEI layer on lithium metal sheet, the mixture formed by the present invention is a uniform mixed phase including lithium metal, which can not only provide lithium ions during the charge and discharge process, but also accelerate the rapid transmission of lithium ions at the interface as SEI, reduce interface polarization, guide the uniform deposition of lithium ions, and improve the anti-dendrite ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0018] Figure 1 The cross-sectional SEM images of the negative electrodes prepared in Example 1 and Comparative Example 5 of the present application; Figure 2 The cross-sectional SEM images of the negative electrodes prepared in Example 3 and Comparative Example 6 of the present application; Figure 3 The symmetrical battery assembled with the negative electrode prepared in Example 1 of the present application is 0.5 mA cm -2 Cyclic performance diagram at current density of ; Figure 4 The symmetrical battery assembled with the negative electrode prepared in Example 2 of the present application is 0.5 mA cm -2 Cyclic performance diagram at current density of ; Figure 5 The symmetrical battery assembled with the negative electrode prepared in Example 3 of the present application is 0.5 mA cm -2 Cyclic performance diagram at current density of ; Figure 6 The symmetrical battery assembled with the negative electrode prepared in Example 4 of the present application is 0.5 mA cm -2 Cyclic performance diagram at current density of ; Figure 7 The symmetrical battery assembled with the negative electrode prepared in Comparative Example 1 of the present application has a voltage of 0.5 mA cm -2 Cyclic performance diagram at current density of ; Figure 8 The symmetrical battery assembled with the negative electrode prepared in Comparative Example 2 of the present application has a voltage of 0.5 mA cm -2 Cyclic performance diagram at current density of ; Fig. 9The symmetrical battery assembled with the negative electrode prepared in Comparative Example 3 of the present application has a voltage of 0.5 mA cm -2 Cyclic performance diagram at current density of ; Fig.10 The symmetrical battery assembled with the negative electrode prepared in Comparative Example 4 of the present application has a voltage of 0.5 mA cm -2 Cyclic performance diagram at current density of ; Fig.11 The symmetrical battery assembled with the negative electrode prepared in Comparative Example 5 of the present application has a voltage of 0.5 mA cm -2 Cyclic performance diagram at current density of ; Fig.12 The symmetrical battery assembled with the negative electrode prepared in Comparative Example 6 of the present application has a voltage of 0.5 mA cm -2 Cyclic performance diagram at current density of ; Fig.13 Cycling performance diagram of a solid-state battery assembled with the negative electrode prepared in Example 1 of the present application at a rate of 1C; Fig.14 Cycling performance diagram of a solid-state battery assembled with the negative electrode prepared in Example 2 of the present application at a rate of 1C; Fig.15 Cycling performance diagram of a solid-state battery assembled with the negative electrode prepared in Example 3 of the present application at a rate of 1C; Fig.16 Cycling performance diagram of a solid-state battery assembled with the negative electrode prepared in Example 4 of the present application at a rate of 1C; Fig.17 A cycle performance diagram of a solid-state battery assembled with the negative electrode prepared in Comparative Example 1 of the present application at a rate of 1C; Fig.18 Cycling performance diagram of a solid-state battery assembled with the negative electrode prepared in Comparative Example 2 of the present application at a rate of 1C; Fig.19 A cycle performance diagram of a solid-state battery assembled with the negative electrode prepared in Comparative Example 3 of the present application at a rate of 1C; Fig. 20 A cycle performance diagram of a solid-state battery assembled with the negative electrode prepared in Comparative Example 4 of the present application at a rate of 1C; Fig.21 For this application Fig. 20 The charge and discharge curve of the solid-state battery in the 10th cycle. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The present invention provides a lithium metal negative electrode, comprising Li, LiM alloy, Li c X, LiY and Li a XY b , where M is a metal element, X is an oxygen element or a nitrogen element, and Y is a halogen; when X is an oxygen element, a=3, b=1, c=2; when X is a nitrogen element, a=5, b=2, c=3.
[0021] In some preferred embodiments, M is selected from one or more of La series elements, In, Al, Bi, Zr, Hf, Sn, and Ge. Y can be one or more of F, Cl, Br, and I.
[0022] The preparation method of the above-mentioned lithium metal negative electrode comprises the following steps: heating and melting lithium metal to obtain molten lithium liquid; adding additives to the molten lithium liquid, keeping the temperature at 200-350°C for reaction for 5-60 min, preferably 30 min, and cooling to obtain a lithium metal negative electrode, wherein the additive is MXY, M is a metal element, X is an oxygen element or a nitrogen element, and Y is a halogen.
[0023] In some preferred embodiments, the additive is MOY, such as LaOCl, InOCl, BiOCl, AlOCl, or LaOF, InOF, BiOF, AlOF, or LaOBr, InOBr, BiOBr, AlOBr, etc.
[0024] In some preferred embodiments, the additive is MNY, such as ZrNCl, SnNCl, HfNCl, GeNCl, or ZrNBr, SnNBr, HfNBr, GeNBr, etc.
[0025] In some preferred embodiments, the amount of the additive added is 2-20% of the mass of the lithium metal, and more preferably 10%.
[0026] The present invention is further described in detail below through specific examples.
[0027] Example 1 A lithium metal negative electrode, the preparation method is as follows: Lithium metal is heated to a molten state at 280°C, and then LaOCl, an additive accounting for 10% of the mass of lithium metal, is added to the molten lithium metal, and the reaction is kept at this temperature for 30 minutes. In this process, a mixed SEI containing Li, LiLa, Li2O, LiCl, and Li3OCl is formed, and a composite lithium metal anode is obtained after cooling. Subsequently, the obtained composite lithium metal anode is rolled into a lithium metal foil with uniform thickness by a roller press.
[0028] Example 2 A lithium metal negative electrode, the preparation method is as follows: Lithium metal is heated to a molten state at 280°C, and then LaOCl, an additive accounting for 20% of the mass of lithium metal, is added to the molten lithium metal, and the reaction is kept at this temperature for 40 minutes. In this process, a mixed SEI containing Li, LiLa, Li2O, LiCl, and Li3OCl is formed, and a composite lithium metal anode is obtained after cooling. Subsequently, the obtained composite lithium metal anode is rolled into a lithium metal foil with uniform thickness by a roller press.
[0029] Example 3 A lithium metal negative electrode, the preparation method is as follows: Lithium metal is heated to a molten state at 280°C, and then an additive ZrNCl accounting for 10% of the mass of lithium metal is added to the molten lithium metal, and the reaction is kept at this temperature for 30 minutes. In this process, a mixed SEI containing Li, LiZr, Li3N, LiCl, and Li5NCl2 is formed, and a composite lithium metal anode is obtained after cooling. Subsequently, the obtained composite lithium metal anode is rolled into a lithium metal foil with uniform thickness by a roller press.
[0030] Example 4 A lithium metal negative electrode, the preparation method is as follows: Lithium metal is heated to a molten state at 200°C, and then GaOF, an additive accounting for 10% of the mass of lithium metal, is added to the molten lithium metal, and the reaction is kept at this temperature for 30 minutes. In this process, a mixed SEI containing Li, LiGa, Li2O, LiF, and Li3OF is formed, and a composite lithium metal anode is obtained by cooling. Subsequently, the obtained composite lithium metal anode is rolled into a lithium metal foil with uniform thickness by a roller press.
[0031] Comparative Example 1 Compared with Example 1, the additive used in Comparative Example 1 is LaCl3.
[0032] A lithium metal negative electrode, the preparation method is as follows: Lithium metal is heated to a molten state at 280°C, and then LaCl3, an additive accounting for 10% of the mass of lithium metal, is added to the molten lithium metal, and the reaction is kept at this temperature for 30 minutes. In this process, a mixed SEI containing Li, LiLa, and LiCl is formed, and a composite lithium metal anode is obtained by cooling. Subsequently, the obtained composite lithium metal anode is rolled into a lithium metal foil with uniform thickness by a roller press.
[0033] Comparative Example 2 Compared with Example 3, the additive used in Comparative Example 2 is ZrCl4.
[0034] A lithium metal negative electrode, the preparation method is as follows: Lithium metal is heated to a molten state at 280°C, and then an additive ZrCl4 accounting for 10% of the mass of lithium metal is added to the molten lithium metal, and the reaction is kept at this temperature for 30 minutes. In this process, a mixed SEI containing Li, LiZr, and LiCl is formed, and then the temperature is cooled to obtain a composite lithium metal negative electrode. Subsequently, the obtained composite lithium metal negative electrode is rolled into a lithium metal foil with uniform thickness by a roller press.
[0035] Comparative Example 3 Compared with Example 4, the additive used in Comparative Example 3 is GaF3.
[0036] A lithium metal negative electrode, the preparation method is as follows: Lithium metal was heated to a molten state at 200°C, and then GaF3, an additive accounting for 10% of the mass of lithium metal, was added to the molten lithium metal, and the reaction was kept at this temperature for 30 minutes. The composite lithium metal anode was obtained by cooling. Subsequently, the composite lithium metal anode was rolled into a lithium metal foil with uniform thickness by a roller press.
[0037] Comparative Example 4 Without any treatment, pure lithium metal is rolled into lithium metal foil with uniform thickness through a roller press.
[0038] Comparative Example 5 (1) LaOCl powder was ultrasonically dispersed in water. Then, the LaOCl suspension was added dropwise onto the Cu foil and dried in an oven to form a LaOCl layer on the Cu foil. The loading amount of the LaOCl powder on the Cu foil was 1 mg cm -2 .
[0039] (2) The LaOCl-Cu and lithium foil are mechanically rolled together; during this period, the LaOCl is transferred to the lithium foil and spontaneously reacts with the lithium metal surface; in order to make the reaction more complete, it is further heated at 200°C; and a lithium metal anode protected by a mixed artificial interface film of LiLa alloy and Li3OCl solid electrolyte is obtained.
[0040] Comparative Example 6 (1) ZrNCl powder was ultrasonically dispersed in water. Then, the ZrNCl suspension was added dropwise onto Cu foil and dried in an oven to form a ZrNCl layer on the Cu foil. The loading amount of ZrNCl powder on the Cu foil was 1 mg cm -2 .
[0041] (2) The ZrNCl-Cu is mechanically rolled together with lithium foil; during this period, the ZrNCl is transferred to the lithium foil and spontaneously reacts with the lithium metal surface; in order to make the reaction more complete, it is further heated at 200 °C; and a lithium metal anode protected by a mixed artificial interface film of LiZr alloy and Li5NCl2 solid electrolyte is obtained.
[0042] 1. SEM Characterization Figure 1 The cross-sectional SEM images of the negative electrodes prepared in Example 1 and Comparative Example 5; Figure 2 The cross-sectional SEM images of the negative electrodes prepared in Example 3 and Comparative Example 6 are shown in FIG. Figure 1 a is comparative example 5, b is example 1, Figure 2 a is comparative example 6, b is example 3. From SEM, it can be seen that the lithium metal negative electrode prepared in the present invention is composed of Li, LiM alloy, LiX, LiY, Li a XY b The mixed structure is a homogeneous structure, while the lithium metal negative electrode prepared in Comparative Examples 5-6 is a double-layer structure, which is based on a lithium metal sheet, and the lithium metal sheet is loaded with an artificial interface membrane composed of an alloy and a solid electrolyte.
[0043] 2. Battery preparation and performance testing 1. Preparation of symmetrical battery: Weigh a certain amount of sulfide electrolyte Li in the glove box 5.5 PS 4.5 Cl 1.5 Cold pressing was performed in a mold. The pressure for forming the sulfide electrolyte layer was controlled at 100 MPa to 400 MPa. Subsequently, the lithium metal foils prepared in the embodiment and the comparative example were attached to both sides of the sulfide electrolyte layer and pressure was applied at 10-100 MPa to obtain 8 symmetrical batteries. -2 The charge and discharge test was carried out at a current density of . The test results are as follows Figures 3 to 12 And as shown in Table 1.
[0044] Table 1
[0045] From Table 1 and Figures 3 to 12It can be seen that the symmetrical battery assembled by the lithium metal negative electrode prepared in the embodiment of the present application has a lower polarization voltage, which means that the internal resistance of the battery is small and the electrode reaction is easier to carry out, thereby improving the energy conversion efficiency and stability of the battery. Compared with Example 3, the polarization voltage of Comparative Example 2 is significantly increased, and short circuit is prone to occur, indicating that the mixed SEI containing Li3N and Li5NCl2 formed by the reaction of the nitrogen element in the additive with lithium metal can improve the anti-dendrite ability, accelerate the transmission rate of lithium ions, reduce the interface polarization, and improve the safety of the battery. The unmodified lithium metal negative electrode of Comparative Example 4 is prone to lithium dendrites piercing the electrolyte layer, causing a short circuit. The polarization voltage of the lithium metal negative electrode prepared by the methods of Comparative Examples 5 and 6 is relatively high, indicating that it has a large internal resistance, which is not conducive to improving the energy conversion efficiency, and a slight short circuit occurs after the 18th cycle.
[0046] 2. Preparation of all-solid-state batteries Preparation of composite cathode: sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 and conductive additive vapor grown carbon fiber (VGCF) and positive electrode material LiNi 0.7 Co 0.1 Mn 0.2 O2 was mixed. During the mixing, the materials were mixed by mechanical mixing, wherein the rotation speed was 300 rpm, the ball milling time was 1.5 hours, and the ball milling was carried out under the protection of high-purity argon (99.999%) to obtain a composite positive electrode. Among them, the mass ratio of positive electrode material: sulfide electrolyte: conductive additive was 70:27:3.
[0047] Preparation of lithium metal battery: weigh a certain amount of sulfide electrolyte powder Li in the glove box 5.5 PS 4.5 Cl 1.5 Cold press molding is performed in a mold with the pressure controlled at 10 MPa to 100 MPa to obtain an electrolyte layer. Subsequently, a certain amount of the composite positive electrode prepared as described above is placed on one side of the electrolyte and pressed under a pressure of 10 MPa to 100 MPa. Finally, the lithium metal negative electrode prepared in the embodiment and the comparative example is attached to the other side of the electrolyte layer and cold press molding is performed in a mold with the pressure controlled at 10 MPa to 350 MPa to obtain 8 solid-state batteries respectively. Charge and discharge tests were performed at a rate of 1C respectively, and the ratio of the capacity after 50 cycles to the initial capacity is the capacity retention rate after cycles. The test results are as follows Figures 13 to 21 shown.
[0048] from Figures 13 to 21It can be seen that compared with Comparative Examples 1 to 4, the lithium metal negative electrode prepared in the present embodiment has good charge and discharge capacity and cycle stability, indicating that by introducing Li, LiM alloy, Li c X, LiY and Li a XY b , which can reduce the formation of lithium dendrites and improve the lithium ion transmission capacity; at the same time, it can enhance the cycle stability and avoid short circuit.
[0049] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For details not described in individual embodiments, reference may be made to the description in other embodiments.
[0050] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A lithium metal negative electrode, characterized in that Contains Li, LiM alloy, Li c X, LiY and Li a XY b , where M is a metal element, X is an oxygen element or a nitrogen element, and Y is a halogen; when X is an oxygen element, a=3, b=1, c=2; when X is a nitrogen element, a=5, b=2, c=3.
2. The lithium metal negative electrode according to claim 1, characterized in that M is selected from one or more of La-based elements, In, Al, Bi, Zr, Hf, Sn, and Ge.
3. The method for preparing a lithium metal negative electrode according to any one of claims 1 to 2, characterized in that: The following steps are involved: The lithium metal is heated and melted to obtain molten lithium liquid; Adding an additive to the molten lithium solution, carrying out a heat preservation reaction, and cooling to obtain the lithium metal negative electrode; the additive is MXY, wherein M is a metal element, X is an oxygen element or a nitrogen element, and Y is a halogen.
4. The method for preparing a lithium metal negative electrode according to claim 3, characterized in that: The additive is at least one of LaOCl, InOCl, BiOCl and AlOCl.
5. The method for preparing a lithium metal negative electrode according to claim 3, characterized in that: The additive is at least one of ZrNCl, SnNCl, HfNCl, and GeNCl.
6. The method for preparing a lithium metal negative electrode according to claim 3, characterized in that: The amount of the additive added is 2-20% of the mass of the lithium metal.
7. The method for preparing a lithium metal negative electrode according to claim 3, characterized in that: The temperature of the heat preservation reaction is 200-350°C.
8. The method for preparing a lithium metal negative electrode according to claim 3, characterized in that: The reaction time of the insulation reaction is 5-60 min.
9. A lithium battery, characterized in that: It comprises the lithium metal negative electrode as described in any one of claims 1 to 2.
10. The lithium battery according to claim 9, characterized in that The electrolyte of the lithium battery is Li 7-x PS 6-x Cl x (0.5≤x≤2), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li7P2S8I、Li 10 GeP2S 12 One or more of; the positive electrode material of the lithium battery is LiNi m Co n Mn z O2 (m+n+z=1).
Citation Information
Patent Citations
Positive electrode active material and battery
CN110048087A
Negative electrode material of Lithium ion battery and preparation method thereof
CN110289414A
Lithium metal negative electrode, preparation method thereof and lithium-ion battery
CN112151759A
Lithium metal negative electrode, preparation method thereof and related lithium metal battery and device
CN114530589A
Preparation method of Li-M alloy negative electrode for sulfide solid-state battery
CN116072824A